Financial Performance Analysis of Nepalese Financial Institutions in the Framework of CAMEL - Gautam, Kedar Raj (Janapriya Journal of Interdisciplinary Studies, 2020)
Analysis of financial performance to detect financial health of finance companies, development banks and commercial banks as a whole is a less explored research in Nepalese context. This paper, therefore, attempts to examine the financial performance and factors influencing financial performance of Nepalese financial depositary institutions in the framework of CAMEL. This study is based on descriptive cum casual research design. This study is based on secondary data which was extracted from various publications published by Nepal Rastra Bank such as banking and financial statistics, financial stability report and bank supervision report. All commercial banks, development banks, and finance companies are taken as population of the study. The study deals with financial performance analysis of entire population covering five years from 2014/15 to 2018/19. The variables such as capital adequacy, assets quality, management efficiency, earnings and liquidity are used to analyze financial performance. Descriptive as well as pooled regression analysis was used to assess the relationship among the variables. Descriptive analysis shows that financial institutions in each category meet NRB standard regarding capital adequacy. On the basis of capital adequacy and earnings, finance companies stand at first, on the basis of assets quality, development banks stand at first and on the basis of management efficiency, commercial banks stand at first. Finance companies store high liquidity as compared to other class financial institutions. The regression analysis shows that return on assets, ROA has significant positive relationship with capital adequacy and ROE but ROA has significant negative relationship with assets quality. However, return on equity, ROE has significant positive relationship with assets quality and ROA but ROE has significant negative relationship with capital adequacy. Capital adequacy and assets quality play major role to maximize ROA and ROE of financial institutions.